Microsoft Forefront UAG 2010 administrator's handbook : take full command of Microsoft Forefront Unified Access Gateway to secure your business applications and provide dynamic remote access with DirectAccess /: take full command of Microsoft Forefront Unified Access Gateway to secure your business applications and provide dynamic remote access with DirectAccess. (2011) - Unknown
No abstract available